(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Myasthenia gravis is a disease of great significance to the anaesthesiologist, because it affects the neuromuscular junctions. Many patients with this condition are treated by surgical thymectomy. Thymectomy for myasthenia gravis requires special attention as far as the type of anesthesia and use of muscle relaxants. We use high thoracic epidural anaesthesia for trans-sternal thymectomy to avoid the use of muscle relaxants and volatile anesthetic agents which prevented the laryngeal injury and potential post-operative respiratory failure. Key words: Myasthenia gravis, Thymectomy. Journal of BSA, 2008; 21(2): 86-87